1990
DOI: 10.1111/j.1365-2044.1990.tb14504.x
|View full text |Cite
|
Sign up to set email alerts
|

A jet nebuliser for delivery of topical anaesthesia to the respiratory tract A comparison with cricothyroid puncture and direct spraying for fibreoptic bronchoscopy

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…VAS score of satisfaction and comfort had been widely used for evaluation of the use of sedation and local anaesthesia in bronchoscopy in various studies and showed good short-term reproducibility. 911,13 Once the patients were fully alert and conscious (usually after 2 hours), we recorded their tolerability for the procedure using VAS to assess their satisfaction and comfort. The VAS of satisfaction and comfort in this study was depicted on a 10 cm horizontal straight line.…”
Section: Visual Analogue Scale and Cough Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…VAS score of satisfaction and comfort had been widely used for evaluation of the use of sedation and local anaesthesia in bronchoscopy in various studies and showed good short-term reproducibility. 911,13 Once the patients were fully alert and conscious (usually after 2 hours), we recorded their tolerability for the procedure using VAS to assess their satisfaction and comfort. The VAS of satisfaction and comfort in this study was depicted on a 10 cm horizontal straight line.…”
Section: Visual Analogue Scale and Cough Assessmentmentioning
confidence: 99%
“…8 Current literature on patient satisfaction towards FFB have mainly focused on comparing satisfaction using different methods of applying local anaesthesia during the procedure. 911 Some studies were performed to compare the effect of sedation towards suppression of cough reflex and patient satisfaction. 12,13 The majority of these studies used a patient and bronchoscopist visual analogue scale (VAS) score of satisfaction or tolerance as measurement for satisfaction and efficacy of FFB.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] No particular technique has proved itself to be consistently better than the other. However, patient cooperation is essential for the procedure to proceed smoothly.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to intubation, upper airway is commonly anaesthetized by lignocaine spray while larynx and lower respiratory tract is anaesthetised by spraying lignocaine directly down the fiberscope side port by spray-as-you-go technique. [7][8][9] The spray-as-you-go technique involves local anaesthetic application while advancing the tip of the fibrescope. The spray-asyou-go technique using fiberoptic bronchoscope provides flexibility in selectively anaesthetizing respiratory passages.…”
Section: Introductionmentioning
confidence: 99%